A recombinant non-toxigenic Clostridioides difficile spore vaccine directed against toxigenic C. difficile - Aston, Carl (2022)
Clostridioides difficile (C. difficile) is the leading cause of hospital acquired diarrhoeal infection. Its pathology is mainly due to two toxins, TcdA and TcdB. The failure to treat recurrent infection can culminate in death and thus preventative measures are of urgent need. Current vaccine trials in humans are exclusively focused on parenteral delivery of toxin-based formulations. While these vaccines elicit toxin-neutralising serum antibody responses, they fail to provide protection against colonisation and therefore Clostridium difficile infection (CDI). Ideally a vaccine targeting C. difficile would aim to generate a local mucosal immune response (i.e., secretory IgA that directly targets the site of infection). In this study, a non-toxigenic strain of C. difficile (NTCD) was utilised as a delivery system, where immunisation with recombinant spores would allow direct delivery of vaccine candidates to the ileum. To provide a mechanism of release from the cell, as well as increase immunogenicity, a fragment of the TcdB receptor binding domain (previously shown to be immunogenic) was fused to the signal peptide of lipoprotein and colonisation factor CD0873 with a view to creating a TcdB antigen which is naturally lipidated. Both this TcdB construct, and full-length CD0873 were utilised as vaccine candidates. Recombinant episomal plasmids were engineered and conjugated into NTCD strain T7, generating strains capable of expressing these vaccine candidates following germination. Western immunoblotting demonstrated the ability of these strains to produce antigens which are secreted into the extracellular milieu. Spores of these recombinant strains were then used to immunise mice and hamsters. Tissues harvested from immunised animals demonstrated a high antigen-specific IgA and IgG titre compared to animals immunised with strains of the wild type T7 strain. They also demonstrated the ability to reduce binding of C. difficile to Caco-2 colorectal cells, and reduce cytotoxicity of TcdB and TcdA to Vero cells. This study provides important proof-of-concept data for use of NTCD strains as a delivery device for vaccine candidates, and paves the way for exploiting the ability of the signal peptide of CD0873 to lipidate and secrete attached antigens to the extracellular milieu.